Translation Quality Assessment of Sustainable Development Goals: (A Cognitive Approach) - Mostafa Taha Abdelhafeez Ali; Dr. Azza Ibrahim Khalil; Dr. Ahmed Abdelmajeed Wafa; Prof. Mohamed Mohamed Tohamy (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This paper examines the cognitive processes involved in the Arabic translation of the Sustainable Development Goals (SDGs) and how these translations impact the interpretation of ecological concepts. Using Gavins’ (2007) Text World Theory, which explores the mental models constructed by readers based on linguistic elements, the research investigates how the Arabic translations of the SDGs activate mental representations within their discourse world. The SDGs’ discourse in Arabic is cognitively organized around four key dimensions: Participants, Place, Time, and Sensory Inputs. These dimensions illustrate how ecological issues are framed and how they influence both global policymaking and individuals’ cognitive engagement with sustainability in the Arabic-speaking world. The analysis specifically focuses on assessing the quality of the Arabic translation, examining how effectively it conveys the intended meanings and how it shapes cognitive understanding of ecological concerns.